Planta turística oferta alojamiento del cantón Salcedo y Saquisilí - Serrano Sinche, Virginia Estefanía (2024)
The objective of this study was to disseminate the current state of the tourist plant offered by the lodging services of the cantons of Salcedo and Saquisilí in the province of Cotopaxi, through an informative bulletin, in order to answer the question regarding the situation of the establishments in the context of the national crisis that the country is undergoing in terms of security and political, social and economic instability, with which the specific objectives were established: A situational diagnosis of the tourist plant of the establishments, which was approached through the application of a survey, an interview and the PESTLA analysis technique, which resulted in the fact that the canton registries are not updated and take into account motels as lodging establishments, as well as the recognition of 10 establishments in the two cantons. Therefore, the need arose to formulate action alternatives to improve the situation, the following objective was to propose operational strategies to strengthen them, which was addressed through a SWOT analysis based on the consideration of the elements that influence the companies and the determination of strategic elements, resulting in improving the administrative process of the establishments, promoting unique experiences through thematic campaigns providing quality services and establishing strategic alliances with local suppliers to ensure the availability of quality services. Finally, a newsletter was designed as a means of dissemination, which was structured based on the information summarized and systematized as an effective communication tool about which establishments are legal in the cantons, peak periods (national holidays, Christmas and New Year's Eve) and off-peak periods (January, before the start of school), price range and the types of tourists who visit. The newsletter will disseminate the results obtained in the study, and if the lodging establishments have a future-oriented approach through the implementation of operational strategies these could help improve the supply of their services.